1992
DOI: 10.1007/bf00227237
|View full text |Cite
|
Sign up to set email alerts
|

Neurons of the motor trigeminal nucleus project to the hypoglossal nucleus in the rat

Abstract: The hypoglossal nucleus (Mo12) contains motoneurons that innervate the tongue, while the motor trigeminal nucleus (Mo5) contains motoneurons that elevate or depress the mandible. Previous studies have revealed lateral and medial tegmental field neuronal afferents to the Mo12 adjacent to, but not within, the motor trigeminal nucleus (Mo5). The current studies demonstrate the presence of retrogradely labeled neuronal afferents to the Mo12 within the Mo5 produced by as little as 10 nl of Fast Blue (FB) injected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…While the injection sites were all well localized to the XII, we cannot exclude from consideration underestimation of the injection site limits due to absorption and transport of the tracer; however, the short survival times utilized make this unlikely. The overall distribution of rhodamine latex beads agrees with previous retrograde studies in our laboratory employing two other fluorescent tracers (Manaker et al, 1992;Manaker and Tischler, 1993), although the current study produced higher absolute numbers of retrogradely labeled neurons using rhodamine latex beads. These differences in absolute numbers of retrogradely labeled neurons may be attributed to the different inherent transport properties of various retrograde tracers (Illert et al, 1982;Craig et al, 1989;Richmond et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While the injection sites were all well localized to the XII, we cannot exclude from consideration underestimation of the injection site limits due to absorption and transport of the tracer; however, the short survival times utilized make this unlikely. The overall distribution of rhodamine latex beads agrees with previous retrograde studies in our laboratory employing two other fluorescent tracers (Manaker et al, 1992;Manaker and Tischler, 1993), although the current study produced higher absolute numbers of retrogradely labeled neurons using rhodamine latex beads. These differences in absolute numbers of retrogradely labeled neurons may be attributed to the different inherent transport properties of various retrograde tracers (Illert et al, 1982;Craig et al, 1989;Richmond et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…The distribution of neurons projecting to the XII observed by the injection of rhodamine-conjugated microspheres in the present study (Tables 1 and 2; Figs. 2 and 3) was similar to previous reports using other retrograde tracers (Takada et al, 1984;Aldes, 1990;Manaker et al, 1992;Manaker and Tischler, 1993). In all eight cases, dense rhodamine labeling was localized bilaterally throughout the lateral tegmental field, especially the parvicellular reticular nuclei.…”
Section: Distribution Of Rhodamine Labelingsupporting
confidence: 86%
“…This finding is consistent with the somatotopic arrangement of the trigeminal motor nucleus in rats (Mizuno et al, 1975;Limwongse and DeSantis, 1977;Sasamoto, 1979;Lynch, 1985;Rokx et al, 1985a,b;Mong et al, 1988), but not all neurons in this region of the trigeminal motor nucleus contained HRP reaction product. Previous studies have reported intranuclear neurons (Shigenaga et al, 1988) and projection (Langer et al, 1985;Røste, 1989;Manaker et al, 1992) and commissural (Mizuno et al, 1978(Mizuno et al, , 1981Ter Horst et al, 1990) interneurons spread throughout the trigeminal motor nucleus. It is likely, therefore, that some of the unlabeled neurons found scattered among the retrogradely labeled neurons in this study are comparable interneurons.…”
Section: Trigeminal Motoneuronsmentioning
confidence: 96%
“…This level of discrimination has become increasingly important when studying trigeminal motoneuronal circuitry because of the diversity of physiological inputs to Vmo (Kidokoro et al, 1968;Nakamura et al, 1973;Ohta and Sasamoto, 1980;Chandler and Goldberg, 1982;Shigenaga et al, 1988;Donga and Lund, 1991;Olsson and Westberg, 1991;Takata et al, 1991;Grimwood et al, 1992;Taylor et al, 1992;Yohsida et al, 1994) and the accumulating evidence indicating that neurons within the trigeminal motor nucleus are not homogeneous. Not only motoneurons, but a variety of interneurons (Mizuno et al, 1978(Mizuno et al, , 1981Shigenaga et al, 1988;Ter Horst et al, 1990;Kolta, 1997) and projection neurons (Langer et al, 1985;Røste, 1989;Manaker et al, 1992) are located within the anatomical confines of the trigeminal motor nucleus. Because some of these interneurons are large enough that they overlap the size range of trigeminal motoneurons (Kotchabhakdi and Walberg, 1977;Mizuno et al, 1981;Ter Horst et al, 1990), the identification of motoneurons should go beyond mere localization within the cytological boundaries of Vmo.…”
mentioning
confidence: 99%
“…Other, presumably non-motoneuronal cells within 5N have central projections, and were retrogradely labeled following injections of retrograde tracers into the cerebellum (cat: Kotchabhakdi and Walberg, 1977;Roste, 1989; rabbit: Bukowska and Grottel, 1997), or hypoglossal nucleus (Manaker et al, 1992). In addition, a small projection from neurons in the jaw-closing region of 5N to the homologous region on the contralateral side could contribute to bilateral jaw closing (Jüch et al, 1993;Ter Horst et al, 1990).…”
Section: Interneuronsmentioning
confidence: 99%